Pengaruh psychological capital terhadap work engagement pada karyawan - Muhammad Husain Hariyadi (Cognicia, 2019)
Work engagement is defined as positive emotions, which is characterized by vigor, dedication, and absorbtion. Psychological capital is positive psychological state of someone who has the following characteristics: self-efficacy, hope, optimism, and resiliency. The purpose of this study is to examine the effect of psychological capital towards work engagement on employee. This study used quantitative method and use ramdom sampling for taking samples. The research subjects were 122 employee. The measurements used were psychological capital question (PCQ) and utrecht work engagement scale (UWES). The data analysis technique uses linear regression methods. The results showed that there was a psychological capital effect on work engagement.